2016
DOI: 10.1007/s11999-015-4387-6
|View full text |Cite
|
Sign up to set email alerts
|

Does Perfusion MRI After Closed Reduction of Developmental Dysplasia of the Hip Reduce the Incidence of Avascular Necrosis?

Abstract: Background Gadolinium-enhanced perfusion MRI (pMRI) after closed reduction/spica casting for developmental dysplasia of the hip (DDH) has been suggested as a potential means to identify and avoid avascular necrosis (AVN). To date, however, no study has evaluated the effectiveness of pMRI in clinical practice or compared it with other approaches (such as postreduction CT scan) to show a difference in the proportion of AVN. Questions/purposes (1) Can a pMRI-based protocol be used immediately post closed reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 38 publications
4
24
0
Order By: Relevance
“…Similar to our results, it was also reported in previous studies [9,17,20] that age was not the risk factor of AVN after CR, while other studies gave the opposite conclusion [11,21,22]. The rate of AVN (15.4%) in this study falls into the range of the previously reported studies (10-33%) [7,[23][24][25][26]. The most common cause of AVN is the immobilization in a position that places excessive pressure on the femoral head.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our results, it was also reported in previous studies [9,17,20] that age was not the risk factor of AVN after CR, while other studies gave the opposite conclusion [11,21,22]. The rate of AVN (15.4%) in this study falls into the range of the previously reported studies (10-33%) [7,[23][24][25][26]. The most common cause of AVN is the immobilization in a position that places excessive pressure on the femoral head.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our results, age was not found to be the risk factor of AVN after CR also reported in other literatures [9,15,20]. The rate of AVN (18.6%) in this present study was similar to previously reported studies (10%-33%) [7] [21][22][23][24]. The most common cause is the immobilization in a position that places excessive pressure on the femoral head.…”
Section: Discussionsupporting
confidence: 91%
“…Although in our study age does not play as a signi cant risk factor for AVN and re-dislocation, Similar to our results, it was also reported in previous studies [9,17,22] that age was not the risk factor of AVN after CR, while other studies gave the opposite conclusion [11,20,21]. The rate of AVN (15.4%) in this study falls into the range of the previously reported studies (10%-33%) [7] [23][24][25][26]. The most common cause of AVN is the immobilization in a position that places excessive pressure on the femoral head.…”
Section: Discussionsupporting
confidence: 90%